Validation of cantilever-enhanced photoacoustic particle-size-resolved light absorption measurement using nigrosin reference particles and Mie modelling - J. Kuula; J. Kuula; J. Karhu; J. Karhu; T. Mikkonen; P. Grahn; A. Virkkula; A. Virkkula; H. Timonen; T. Hieta; T. Hieta; M. Vainio; et al. (Aerosol Research)
Particle light absorption enhancement, also known as the lensing effect, is a complex phenomenon where particles undergo optical transformation as they age. This process is influenced by several factors, including particle size. To investigate the lensing effect, this study introduces and validates a novel method for size-resolved light absorption measurements using nigrosin particles as a model system. The method combines a three-wavelength cantilever-enhanced photoacoustic spectrometer (CEPAS) with a differential mobility analyser (DMA) to achieve particle-size-resolved measurements. Nigrosin, a well-characterised, spherically shaped, and water-soluble material, was selected to demonstrate the feasibility and precision of the approach. The system showed strong agreement (R2>0.94) with Mie-modelled absorption, confirming its reliability. While the broader motivation for this work lies in advancing techniques for studying ageing, coating, and absorption enhancement in black carbon and other atmospheric aerosols, the present study serves as a foundational step by validating the methodology in a controlled and simplified context. Future studies will expand the application of this method to complex systems, including coated and aggregated black carbon particles, to explore phenomena such as absorption enhancement.